Evolution, Expression Patterns, and Distribution of Novel Ribbon Worm Predatory and Defensive Toxins. (5th May 2022) - Verdes, Aida; Taboada, Sergi; Hamilton, Brett R.; Undheim, Eivind A.B.; Sonoda, Gabriel G.; Andrade, Sonia C.S.; Morato, Esperanza; Marina, Ana Isabel; Cárdenas, César A.; Riesgo, Ana
Abstract: Ribbon worms are active predators that use an eversible proboscis to inject venom into their prey and defend themselves with toxic epidermal secretions. Previous work on nemertean venom has largely focused on just a few species and has not investigated the different predatory and defensive secretions in detail. Consequently, our understanding of the composition and evolution of ribbon worm venoms is still very limited. Here, we present a comparative study of nemertean venom combining RNA-seq differential gene expression analyses of venom-producing tissues, tandem mass spectrometry-based proteomics of toxic secretions, and mass spectrometry imaging of proboscis sections, to shed light onto the composition and evolution of predatory and defensive toxic secretions in Antarctonemertes valida . Our analyses reveal a wide diversity of putative defensive and predatory toxins with tissue-specific gene expression patterns and restricted distributions to the mucus and proboscis proteomes respectively, suggesting that ribbon worms produce distinct toxin cocktails for predation and defense. Our results also highlight the presence of numerous lineage-specific toxins, indicating that venom evolution is highly divergent across nemerteans, producing toxin cocktails that might be finely tuned to subdue different prey. Our data also suggest that the hoplonemertean proboscis is a highly specialized predatory organ that seems to be involved in a variety of biological functions besides predation, including secretion and sensory perception. Overall, our results advance our knowledge into the diversity and evolution of nemertean venoms and highlight the importance of combining different types of data to characterize toxin composition in understudied venomous organisms.